(untitled) (Research, Society and Development, 2022)
Polymeric materials are increasingly present in everyday life and are discarded on a large scale constituting a challenge for its recycling. This work studied the depolymerization of expanded polystyrene (EPS) waste through microwave using carbon black as catalyst. The catalytic pyrolysis was investigated at five catalysts to polymer ratios (0.0125:1, 0.125:1, 0.25:1, 0.5:1, 1:1). The microwave assisted pyrolysis occurred at 400 W in a fixed time of 12 minutes. Fourier Transform Infrared Spectroscopy (FTIR) and thermogravimetric analysis (TGA) were performed to evaluate the depolymerization. The highest yield of non-condensable gases was obtained at the ratio 0.25:1 with a gaseous yield of 53%. FTIR analysis from liquid fraction of the ratio 0.25:1 showed new absorption bands and new degradation peaks at lower temperatures were observed in thermogravimetry when compared with EPS waste. This study demonstrated the possibility of depolymerization of EPS via microwave using carbonaceous structures, which may contribute to EPS recycling.